2000
DOI: 10.1056/nejm200008103430603
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Suture Repair with Mesh Repair for Incisional Hernia

Abstract: Among patients with midline abdominal incisional hernias, mesh repair is superior to suture repair with regard to the recurrence of hernia, regardless of the size of the hernia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
882
4
55

Year Published

2002
2002
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,666 publications
(954 citation statements)
references
References 25 publications
13
882
4
55
Order By: Relevance
“…Suture repair of incisional hernia results in recurrence rates of 12% to 54%, 10 -16 while mesh repair results in recurrence rates of 2% to 36%. [13][14][15][17][18][19][20][21][22][23] Because most studies only provide shortterm follow-up, these recurrence rates may even be underestimated. In addition to the high recurrence rates, incisional hernia repair may give rise to serious complications, such as enterocutaneous fistula and bowel obstruction, causing deterioration rather than improvement of the patient's situation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Suture repair of incisional hernia results in recurrence rates of 12% to 54%, 10 -16 while mesh repair results in recurrence rates of 2% to 36%. [13][14][15][17][18][19][20][21][22][23] Because most studies only provide shortterm follow-up, these recurrence rates may even be underestimated. In addition to the high recurrence rates, incisional hernia repair may give rise to serious complications, such as enterocutaneous fistula and bowel obstruction, causing deterioration rather than improvement of the patient's situation.…”
mentioning
confidence: 99%
“…14 Unfortunately, there have not been randomized trials of incisional hernia repair since, and some authors have even suggested that there may still be a place for suture repair of incisional hernia. 15,24,25 Disconcerting data indicate that surgeons are still performing suture repair, in spite of clinical evidence.…”
mentioning
confidence: 99%
“…This has resulted in the introduction of prosthetic meshes to correct fascial defects, and randomized clinical studies have indeed proven the superiority of prosthetic meshes in the repair of inguinal [7] and incisional [2,12] hernias, making their usage almost obligatory in these cases.…”
mentioning
confidence: 99%
“…Their repair with a synthetic non-absorbable mesh to reinforce the abdominal wall leads to a significant decrease of nearly 50% in the hernia recurrence rate [2-4]. …”
Section: Introductionmentioning
confidence: 99%